Flow characteristics of Au-blood nanofluid in stenotic artery. (October 2021) - Sarwar, Lubna; Hussain, Azad
Abstract: This article discussed the flow characteristics of human blood under stenoses assumptions. The human blood is considered as Newtonian fluid. The problem governing equations along with the boundary conditions are reduced to dimensionless form by using appropriate similarity transformation to obtain the numerical solution of velocity and temperature of blood flow through stenosed artery. The flow quantities are calculated at cylindrical surface and results are also shown through graphs and tables. Gold nanoparticles can improve the flow of blood and could be a promising therapeutic approach against arterial diseases as compared to Cu and Al2O3-NPs. Results shows that velocity and temperature of blood decreases by increasing the size of gold nanoparticles. Additionally, the skin friction and heat transfer analysis for the blood flow dynamics is also examined. It is noticed that by increasing the values of flow parameter, heat transfer rate and skin friction coefficient decreases. To predict the reason of the atherosclerosis, the modeling and numerical solution plays an incredible role. Graphical abstract: Unlabelled Image